Enhancing Vinyl Chloride Product Yield By Optimizing Operating Conditions In Plug Flow Reactor With Al2O3 Catalyst - Fauziyah, Almas; Ratnawati, Ida; Shafura, M. Regina Lintang; Anggraini, Widia Ayu (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
Vinyl chloride (VC) is a colorless stable gas produced through a complex process with many interactions in reaction and separation. This study aims to improve mass and energy efficiency in vinyl chloride production through process simulation with HYSYS V.11. The process was modified using a plugged flow reactor (PFR) with an Al2O3 catalyst and a simplified distillation column. The method involves recycling the liquid product from the distillation column back to the mixing unit as a feed. The results show that energy efficiency improves with the reduction of the reactor's heat flow requirement from 1.009×107 kJ/h, and to 4.689×106 kJ/h, and distillation of the 2.82×106 kJ/h to 1.368×106 kJ/h. Mass efficiency also increased, with vinyl chloride yields rising by 118%, from 2572 kg/h to 3045 kg/h. In conclusion, these process modifications have succeeded in reducing energy consumption and increasing production significantly, making the process more efficient and energy friendly. Further research is suggested to optimize the use of waste heat. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).